2023
DOI: 10.1038/s41467-023-40704-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and selective capture of thorium ions by a covalent organic framework

Xiaojuan Liu,
Feng Gao,
Tiantian Jin
et al.

Abstract: The selective separation of thorium from rare earth elements and uranium is a critical part of the development and application of thorium nuclear energy in the future. To better understand the role of different N sites on the selective capture of Th(IV), we design an ionic COF named Py-TFImI-25 COF and its deionization analog named Py-TFIm-25 COF, both of which exhibit record-high separation factors ranging from 102 to 105. Py-TFIm-25 COF exhibits a significantly higher Th(IV) uptake capacity and adsorption ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The solid was isolated by centrifugation and washed with DMAC and THF, followed by Soxhlet extraction with THF for 24h. The FT-IR spectrum of 1D-18C6-COF contains a strong peak at 1624 cm –1 which indicated the formation of CN linkages, coincident with the disappearance of bands from amino N–H of TAPPy (3212 and 3346 cm –1 ) and aldehydic CO of B18C6 (1694 cm –1 ) (Figure b). The 13 C CP-MAS NMR spectrum of 1D-18C6-COF exhibited intense peaks at 71 and 158 ppm, stemming from the carbon atoms of 18C6 and imine, respectively (Figure c).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The solid was isolated by centrifugation and washed with DMAC and THF, followed by Soxhlet extraction with THF for 24h. The FT-IR spectrum of 1D-18C6-COF contains a strong peak at 1624 cm –1 which indicated the formation of CN linkages, coincident with the disappearance of bands from amino N–H of TAPPy (3212 and 3346 cm –1 ) and aldehydic CO of B18C6 (1694 cm –1 ) (Figure b). The 13 C CP-MAS NMR spectrum of 1D-18C6-COF exhibited intense peaks at 71 and 158 ppm, stemming from the carbon atoms of 18C6 and imine, respectively (Figure c).…”
Section: Resultsmentioning
confidence: 96%
“… After the adsorption of Sr, the N 1s spectrum can be fitted into two peaks located at 399.9 and 399.2 eV, which correspond to the N atom in C–N and CN. No new peak below 399 eV was found, indicating the lack of interaction between N and Sr . The O 1s spectrum can be deconvoluted into three peaks located at 533.5, 533, and 532 eV (Figure c).…”
Section: Resultsmentioning
confidence: 97%
“…This nucleophilic substitution reaction induces structural changes in the amino functional group and gives rise to the appearance of characteristic peaks corresponding to –NH– in the infrared spectrum. 43–46 The characteristic stretching vibration peak attributed to the –CN– bond in the ionic liquid manifests at a wavenumber of 1580 cm −1 . By comparing and analyzing the infrared spectra, it can be concluded that Gd-TPTC-NH 2 was successfully used as the mother material to prepare the composite material Gd-TPTC-NH-[BMIM]Br, loaded with the ionic liquid.…”
Section: Resultsmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) possess great potential to become important candidates in NCA 177 Lu separation. Well-defined microstructures and highly modifiable functionality endow COFs with wide applications in catalysis, proton conduction, membrane separation, etc. In the last two decades, COFs have exhibited good application prospects for applied isotopes, including H 2 /D 2 separation, I 2 capture, Xe/Kr isolation, and actinide enrichment. However, there is still no work on applying COFs into medical radionuclide separation. Currently, functional COFs utilized in various fields are usually decorated by irreversible covalent avenues, mainly based on side chains branched through either pre- or postgrafting, according to the specific requirements of corresponding applications. This kind of chemical functionalization is not workable when a trace number of medical radionuclides are required to extract from a macro amount of target materials, especially under extreme conditions including high-dose irradiation, strong acid/base, and multiple competing components.…”
Section: Introductionmentioning
confidence: 99%